Judicial Attitude To Environmental Litigation And Access To Environmental Justice In Nigeria: Lessons From Kiobel - Mmadu, Rufus Akpofurere (Journal of Sustainable Development Law and Policy, 2025)
This paper examines judicial attitude to environmental litigation and access toenvironmental justice in Nigeria. The paper employs expository analysis as its methodology indiscussing the theme. Essentially, the paper finds that environmental litigations in Nigeria arebedeviled by legal technicalities such that victims of environmental pollution and degradation areultimately denied access to justice. Ranging from issue of locus to territorial and subject matterjurisdiction, victims of oil spill and environmental degradation are often left without judicialremedies. The paper finds that consequently, the people of the Niger Delta are increasingly losingconfidence in the judiciary both at the domestic and international level. This has heightened militancyand youths’ restiveness in the area leading to loss of revenues and sometimes lives.The paper notes with concern the recent trend of outsourcing justice, as evident in attemptsto bring environmental pollution cases in Nigeria before domestic courts abroad. For example thecelebrated case of Kiobel v Royal Dutch Shell, heard in United States of America. Kiobel isarguably a setback to this approach of searching for environmental justice before international courtsand a reminder on the need to look inwards. This paper calls for judicial flexibility and a moreproactive approach to legal reasoning by Nigerian courts, in order to put environmental matters onthe front burner of our national discourse. Unless and until environmental justice is entrenched inNigeria through judicial activism, Governmental inertia and unwillingness to provide remedies forvictims of environmental degradation may continue to fuel militancy in the years ahead.